2020
DOI: 10.3390/en13061359
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Work Productivity and Costs of a Stationary Chipper Applied to the Harvesting of Olive Tree Pruning for Bio-Energy Production

Abstract: Pruning residues could represent an important biomass resources for energy production. Only in Italy it has been estimated that an annual quantity of biomass of over 2600 kt of dry matter could be obtained from olive residues. Several machines developed for pruning harvesting are available in the market, most of which are tractor-driven, while limited knowledge is available on performance, quality of work and costs of harvesting logistics based on stationary chippers. The aim of the present paper is to analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 23 publications
(36 reference statements)
0
16
1
Order By: Relevance
“…In contrast, the SAT-4 and Jordan presented better performances for this variable with 6.01 t fm •h −1 and 6.7 t fm •h −1 , respectively. Finally, Suardi et al [43] reported a very high material capacity of 7.26 t fm •h −1 with a Caravaggi Bio900 stationary chipper.…”
Section: Machine Performance and Quality Of The Work And Woody Comminmentioning
confidence: 97%
“…In contrast, the SAT-4 and Jordan presented better performances for this variable with 6.01 t fm •h −1 and 6.7 t fm •h −1 , respectively. Finally, Suardi et al [43] reported a very high material capacity of 7.26 t fm •h −1 with a Caravaggi Bio900 stationary chipper.…”
Section: Machine Performance and Quality Of The Work And Woody Comminmentioning
confidence: 97%
“…Apple pruning seems, instead, to be a better material for pelletization, with an ash content and LHV that met the ISO standards; however, problems linked to a low bulk density have been detected [74]. Regarding the issue of pellet production from pruning residues, a key aspect to be further investigated is the economical sustainability of the supply chain, considering that pruning collection represents a certain cost by itself [75,76], also in this case an interesting solution could be the development of mobile technologies for pellets production at the farm, thus limiting supply chain costs [73].…”
Section: Pure Feedstock For Pellet Productionmentioning
confidence: 99%
“…Then, a hydraulic loader feeds the chipper which, in turn, unloads the comminuted material on the ground. Then a lifter collects and load it on a truck for transport [11]. This represent the third harvesting scenario (SC) which consists of the use of the stationary chipper and it is considered for a slope ranging from 25 to 30%.…”
Section: Average Pruning Biomass and Harvesting Scenariosmentioning
confidence: 99%
“…European, national and regional laws particularly encourage small size biomass power plants (≤1 MWe) powered by local biomass [8][9][10] like the Fiusis power plant situated in the south of Italy (Fiusis s.r.l, Calimera, Apulia). Fiusis represents a successful and unique case in Europe of short supply chain of local olive tree pruning used for electricity production [11]. It relays on an innovative logistic chain of the biomass suppling that is not bought from external enterprises as generally happens for conventional power plants.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation